The omission of pronouncement on the arguments of the administered as grounds for nullity of the administrative act - Linares San Román, Juan José (2024)
The present work deals with the omission of pronouncement by the administration in relation to the arguments and evidence presented by the administered, a situation that has not deserved further development in the doctrine addressed in it, but that has been considered as a cause of nullity of the administrative act in certain judicial decisions, given that the principle of due administrative procedure is violated and the motivation requirement is breached and, therefore, the right of defense of the company is strongly affected. In this line, it is convenient to deepen and disseminate this omission as grounds for nullity of the administrative act.